REDUCTIVE ROASTING OF IRON-RICH MANGANESE OXIDE ORE WITH ELEMENTAL SULFUR FOR SELECTIVE MANGANESE EXTRACTION - You, Zhixiong; Li, Guanghui; Peng, Zhiwei; Zhang, Yuanbo; Qin, Li; Jiang, Tao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
It is very important to selectively reduce manganese oxide over iron oxide for extraction of Mn from iron-rich manganese ore. In this study, reductive roasting of an iron-rich manganese oxide ore with elemental sulfur as reductant was investigated. The experimental results demonstrated that manganese dioxide can be selectively reduced with elemental sulfur and extracted via acid leaching, which was largely depended on the sulfur addition. Lower sulfur addition (S/Mn molar ratio2.0) and the roasting temperature exerted a significant impact on the phase composition of roasted product.